Environmental exposure and potential health impact of heavy metals in previous mining communities in Ghana - Opoku, R.B.; Dankyi, E.; Christian, A.; Aryeetey, R. (HSI Journal, 2024)
Heavy metal exposure arising from metal mining is a significant source of pollution in sub-Saharan Africa. In Ghana, concerns have been heightened due to increasing artisanal mining activities. Although efforts are being made to curb illegal mining activities, including a ban on artisanal mining by the government of Ghana, the devastating impacts of mining activities can persist in the environment for a long period. This study was carried out to assess the impact of mining activities on the exposure of toxic and potentially toxic metals in food, vegetation, soil, and water samples from communities where mining activities have been halted for several years. The samples were digested using a microwave digestion system employing a mixture of nitric acid and hydrogen peroxide and analyzed for mercury (Hg), lead (Pb), chromium (Cr), copper (Co), manganese (Mn), zinc (Zn), arsenic (As), cadmium (Cd), cobalt (Co), nickel (Ni), and iron (Fe), using an inductively coupled plasma-mass spectrometer (ICP-MS). The results showed generally elevated levels of metals in water, food, vegetation, and soils. For example, in vegetation, the average concentrations of Pb, Hg, Cd, and As were 198 μg/kg, 303 μg/kg, 75 μg/kg, and 519 μg/kg, respectively, while the average levels of As and Pb were 11,111 μg/kg, and 3,518 μg/kg, respectively, in soil samples collected from abandoned mining sites. Food crops (cassava and plantain samples) grown in abandoned mining fields had elevated levels of Pb (602 μg/kg) and Hg (15.7 μg/kg). Based on our findings of widespread exposure, high concentrations, and potential health risks posed by these metals, proactive measures for the reclamation and remediation of affected land are needed to protect the environment and human lives in these previous mining communities.
Research Article
Keywords: Mining; galamsey; food system; water; health risk; heavy metals; Ghana